The Newest Vital Sign's Impact on Provider Communication - (:unkn) unknown (My University, 2014)
Despite the growing concern over the issues related to low health literacy there has been little research done on the connection between health literacy screening and patient-provider communication. This study thus explores whether or not reporting scores from the health literacy screening tool the Newest Vital Sign (NVS) increases the use of certain techniques recommended for communicating with patients who have low health literacy. Data was collected at the Sixteenth Street Community Health Center at Parkway as part of the Health Literacy Performance Improvement Module by the American Board of Pediatrics. Before pre- and post-conditions began, participating pediatricians were given a brief education session on the concerns related to health literacy and the recommended techniques for communicating with patients who have low health literacy. Between the conditions an intervention was administered that consisted of another education session on the NVS and the teach-back technique specifically. NVS scores were not reported to the pediatricians in the pre-intervention condition, while it was reported in the post-intervention condition. Results indicate the intervention and reporting of NVS scores did increase the use of the teach-back technique. Patient satisfaction also increased after the intervention. On the other hand, the other recommended communication techniques were not used more frequently by pediatricians, probably because they were already utilized at a high rate, even prior to the intervention. Though teach-back did increase after the intervention, more research should be done to further investigate the utility of health literacy screening as well as ways to efficiently increase the rate of the teach-back technique.
Keywords: Literacy